Specialized Accounting Inspection: study on the perception of the Trial judges in the Labor Court System about the quality and relevance of the specialized investigation job of experts - Neves Júnior, Idalberto Jose das; Moreira, Simone Alves; Ribeiro, Elisangela Batista; Silva, Moacenira Cardoso da (Review of Business Management, 2013)
The court appointed experts have means to inform and elucidate the judge, guiding him in his decisions, since it can’t be expected that judges are scientists or technicians in all matters, since there are matters that need clarification and certification of professionals deserving full faith in all technical, moral, scientific and legal aspects. Thus, the burden shouldered by the Judge is shared with the Expert who instructs him with the certification of causes and events through his expertise and requirements of morality and honesty. Within this context, this study aimed to know the opinion of the Trial judges working in the Labour Court System on the quality and relevance of the work done by the accounting expert. To this end, we have carried out a field research with 135 Trial judges of the Labor Court System in all regions of Brazil. The multivariate statistical technique of cluster analysis was used to better study the cases. The results of this survey revealed that 58% of respondents regard the work of the expert accountant as good and necessary, and that 71% of the judges consider the work of the expert accountant relevant to support their decisions. However, the judges have shown the main failures found in the work of the accountant-expert as well as suggestions for improvement.